DAMPAK PENGGUNAAN GAWAI TERHADAP PERKEMBANGAN MORAL ANAK USIA 5 – 6 TAHUN - Y, Yusnia; Fatimah, Sitti; Syam, A. Sri Mardiyanti (EDUCHILD (Journal of Early Childhood Education), 2023)
This study aimed to determine the use of gadgets in children aged 5-6 years in Talungeng Village, Barebbo District, Bone Regency and to determine the impact of gadgets on the morale of children aged 5-6 years in Talungeng Village, Barebbo District, Bone Regency. which uses descriptive qualitative research with pedagogic, psychological and sociological approaches to obtain the desired data using primary and secondary data. Then analyzed by: 1. Reducing the data, 2. presenting the data, and 3. drawing conclusions. The results of this study indicate that there are two forms of using gadgets in children aged 5-6 years in Talungeng Village, Barebbo District, Bone Regency, namely children often access YouTube applications, games and also Tiktok applications and children use different times, children use gadgets with duration under 1 hour, 1 hour and 2 hours a day which is used repeatedly and each use takes 10-15 minutes. There are two impacts of using gadgets on children's morals, namely positive and negative impacts. The positive impact of gadgets for children is that they can train and improve intelligence in terms of knowing literacy, thinking power, high curiosity and can also increase self-confidence for children. The negative impact is that the child has not been able to manage the time of using the device, emotions that still need to be controlled, showing angry emotions, crying, rebelling and even saying disrespectful words to parents and other people.